Ukhuwah Islamiyah Sebagai Spirit Pembangunan Ekonomi Umat (Wacana Zakat Sebagai Tonggak Kemajuan Umat Islam) - Selamet Hartanto (ITB AAS INDONESIA Surakarta, 2023)
Humans are creatures created by God who are naturally also social creatures who cannot live without the help of others. Islam is a religion of rahmatan lil 'alamin It has become a must for every Muslim to maintain good relations, both within the family, community, and with others Country. In the teachings of Islam all humans are equal in status in the eyes of Allah, the only difference is the level of one's piety. Islam educates its people forbids being individualistic, but always instructs its people to always establish relationships with each other, which in religion is known as ukhuwah . islamiyah . Islamic Brotherhood This should be a new spirit in religious life, so that religion creates a soothing atmosphere, not one that spreads hatred. ukhuwah (brotherhood) with Muslims does not become ukhuwah Islamiyah , when it is accompanied by an attitude of mutual harm and oppression. However, when brotherhood with other people despite different beliefs, at that time the brotherhood becomes ukhuwah Islamiyah .